2018
DOI: 10.1016/j.jpainsymman.2017.09.017
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Androgen Deprivation Therapy on Pain Perception, Quality of Life, and Depression in Men With Prostate Cancer

Abstract: ADT in men with PCa is associated with worsening of depression scores and QOL but is not associated with changes in clinical pain or pain sensitivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 53 publications
(55 reference statements)
2
13
1
Order By: Relevance
“…The GDS scores were higher in the second assessment, implying an increase of the men who had a positive screening for depressive symptoms, but the differences were not statistically significant. This finding contrasts with previous longitudinal studies that found a higher prevalence of depression in men treated with ADT [ 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 ], and in line with others, that did not confirm such a relationship [ 73 , 74 ]. Earlier studies suggested a relationship between borderline or lower testosterone levels and depressive symptoms in men [ 75 , 76 , 77 ], especially when the reduction of testosterone concentrations was longitudinal [ 78 ].…”
Section: Discussioncontrasting
confidence: 99%
“…The GDS scores were higher in the second assessment, implying an increase of the men who had a positive screening for depressive symptoms, but the differences were not statistically significant. This finding contrasts with previous longitudinal studies that found a higher prevalence of depression in men treated with ADT [ 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 ], and in line with others, that did not confirm such a relationship [ 73 , 74 ]. Earlier studies suggested a relationship between borderline or lower testosterone levels and depressive symptoms in men [ 75 , 76 , 77 ], especially when the reduction of testosterone concentrations was longitudinal [ 78 ].…”
Section: Discussioncontrasting
confidence: 99%
“…It is possible that a modest positive effect of TRT on pain modulation could wear off during prolonged treatment. In accordance, 6 months androgen deprivation therapy in men with prostate cancer resulted in worsening of depression scores and Qol, whereas pain sensitivity and clinical pain were unchanged (22). Available data do not support any clinically significant effects of long-term TRT on clinical and experimental pain, but future studies should discriminate between short and long-term effects of TRT on pain modulation.…”
Section: Pain Perceptionmentioning
confidence: 90%
“…The pain signals are transmitted via sensory neurons in the peripheral nervous system, expressing receptors and channels that respond to mediators secreted from inflammatory cells (46). Timing with meals, satiety (47), circadian hormonal changes (48)(49)(50)(51)(52), and function of liver enzymes (53) may also be associated with circadian changes.…”
Section: The Circadian Rhythm Underlies the Machinery Of Chronic Painmentioning
confidence: 99%